Development of Interactive Learning Media Based on Powerpoint on Learning IPAS Material Elementary School Plant Body Parts - Mas’ula, Fitri; Putri, Rizki Amalia; Asrofi, Ahmad Jauhar; Murni, Arie Widya; Syväjärvi, Mikael (Islamic Journal of Integrated Science Education (IJISE), 2025)
This research aims to develop interactive learning media based on PowerPoint in the learning of Natural and Social Sciences (IPAS) for the material of plant body parts in elementary schools. The research method uses the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The analysis stage is used to identify learning needs and student characteristics. At the design stage, the media is designed with relevant visual content and supports interactivity. The results of the development are then implemented in the classroom and evaluated through observation, interviews, and questionnaires. The results show that this learning media improves students' understanding plant body parts material and increases learning motivation. Features such as animation and multiple choice evaluation help students understand the material more concretely and interestingly. Teachers also find it helpful as it presents the material in a systematic and structured way. With this media, the learning process becomes more effective, interesting, and relevant to the needs of students in the digital era. This research recommends training for teachers and further development for other IPAS materials.